Psoriasis arising on previous pityriasis rosea. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
A 9-year-old girl was first observed due to a poorly symptomatic rash of the trunk. Her parents reported that two months before first appeared in the left subcostal region a red spot which quickly extended to the periphery and that after about 35 days other smaller lesions appeared on the trunk, mostly in hypogastric region. The physical examination showed a dozen lesions distributed on the trunk: the largest lesion in the left subcostal region was an erythematous patch with clear-cut borders covered by multilayered psoriatic scales (Fig. 1). The smaller lesions were peripherally erythematous with a tendency to central resolution; in some of them there was a scaling intermediate edge which separated the peripheral erythema from to central resolution area and was reminiscent of pityriasis rosea (Fig. 2 and inset). The distribution of the lesions, the frankly psoriasiform appearance of the first more extensive patch, the pityriasiform appearance of the smaller lesions led to the final diagnosis of psoriasis arising on previous pityriasis rosea as an expression of Koebner phenomenon.